The furr-recovery method: Interacting with furry co-workers during work time Is a micro-break that recovers workers’ regulatory resources and contributes to their performance - Junça Silva, A. (International Journal of Environmental Research and Public Health, 2022)
Drawing on the conservation of resources theory and the recovery step model our research expands on a cognitive (regulatory resources) mechanism that links human–animal interactions and employee performance. This study aimed to explore whether daily human–animal interactions during worktime would be conceived as a daily-recovery process that restores the individual’s daily regulatory resources and, as a result, improves daily adaptive and task performance. To test this, a daily diary study during 10 working days, with 105 teleworkers was performed (N = 105 × 10 = 1050). Multilevel results demonstrated that daily interactions between human and their pets served to recover their daily regulatory resources that, in turn, improved daily task-and-adaptive performance. This research not only expands our theoretical understanding of regulatory resources as a cognitive mechanism that links human-animal interactions to employee effectiveness but also offers practical implications by highlighting the recovery role of interacting with pets during the working day, as a way to restore resources needed to be more effective at work.